Analisis Kinerja Keuangan Digital Startups Sebelum dan Sesudah Initial Public Offering di Bursa Efek Indonesia pada Tahun 2017 dan 2018 - Rafa Dwisono; Nenden Kostini; Mas Rasmini (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
The objective of this research is to analyze the differences of financial performance before and after Initial Public Offering digital startups which are listed in Indonesian Stock Exchange in 2017 and 2018. The sample of this research is all of digital startups which are listed in Indonesian Stock Exchange in 2017 and 2018. The sample is 5 digital startups. This research used Paired Sample t-test and Wilcoxon Sign test as the data analysis. The finding indicated financial performance which calculated by debt to asset ratio was significant difference on digital startups between before and after Initial Public Offering. The result of this research indicated that the financial performance of digital startups before and after Initial Public Offering had an insignificant difference. The financial performance of digital startups increased after Initial Public Offering.